The Local Church as a Network Supporting Adults with Disabilities in the Community: One Perspective - McNair, Jeff (Journal of religion, disability & health, 2000)
Using a set of criteria developed for network evaluation, the "local church" is discussed as a network for individuals with developmental disabilities. Although this article only expresses one author's perspective, it provides points for further discussion of both network evaluation, and the local church as a support network for individuals with various disabilities.